Perfectly Matched Layer for Cole-Cole Dispersive Media in DGTD Method - Qin, Xuebin; Wu, Xuan; Wang, Shuo; Zhao, Xiaoying; Zhou, Yuanguo; Ren, Qiang (IEEE journal on multiscale and multiphysics computational techniques, 2024)
Simulating electromagnetic waves within biological tissues is critical for assessing electromagnetic effects in biological environment. Precise modeling of biological tissues in computational electromagnetics is therefore necessary. The Cole-Cole dispersive model based on the fractional power functions can more accurately describe the electrical characteristics of biological tissues in a wide frequency range than the typical dispersive model based on the integer power functions. Previous research on the time-domain simulation of the Cole-Cole medium is mainly based on the finite difference time domain (FDTD) method. Recently, researchers proposed a DEH scheme (Maxwell's equations with field variables D, E and H) discontinuous Galerkin time domain (DGTD) method to simulate wave propagation in the Cole-Cole dispersive media. However, it lacks the perfectly matched layer (PML) to truncate the Cole-Cole background media. This paper fills this gap by developing a PML for Cole-Cole background media in the DGTD method.